The reality and obstacles of teaching Saudi Arabian Sign Language (SASL) to hearing students in regular schools: Alshams Private School as a model - Alamri, Abdulhadi A. (Frontiers in Education, 2024)
This study investigated the reality and obstacles of teaching Saudi Arabian Sign Language (SASL) to hearing students in regular schools. A descriptive survey methodology was employed using a researcher-developed questionnaire. The sample included 148 participants, comprising 94 male and 54 female fifth-and sixth-grade students from Alshams Private School in Riyadh, Saudi Arabia. The findings revealed several obstacles, including the absence of Deaf sign language teachers, limited availability of different levels or courses for sign language instruction, occasional student embarrassment, and challenges related to the learning environment and resources. Significant differences were observed between male and female students in their perceptions of SASL instruction's feasibility, with female students demonstrating a more positive outlook. However, no gender-based distinctions were evident regarding perceived obstacles or overall questionnaire responses. Similarly, no significant differences emerged between fifth-and sixth-grade students in their perceptions of obstacles or questionnaire responses. These findings provide insights into challenges and student perceptions of SASL instruction in Saudi Arabian schools, offering a basis for further research and potential enhancements in sign language education.